Exploring English Literacy Insights From SMA Negeri 1 Hawu Mehara Students Activities - Novriani Rabeka Manafe; Herlyn Sepriana Ully (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study was to identify the elements that helped and hindered the implementation of English literacy programs at SMA Negeri 1 Hawu Mehara. The descriptive qualitative method is used in this study. Open-ended questionnaires, interviews, and observation are the methods utilized to collect data. Students, librarians, English teachers, and school principals are the research's data sources. Based on the data, the author examines and discusses the factors that help and impede English literacy in SMA Negeri 1 Hawu Mehara. Two factors help. 1. internal elements, such as the students' condition, interest, motivation, and mode of learning. 2. External variables, specifically the community and the parents of students. English literacy is hampered by several internal and external factors, such as low student motivation and students who spend a lot of time on social media for play rather than to promote an English-literate culture. Other external factors include government and teacher support for the implementation of English literacy programs.